Pastoral Accompaniment for Final-Year Students Experiencing Future Anxiety - Frans Pantan; Dapit Sameleh; Gideon Hery Susanto (International Journal of Christian Education and Philosophical Inquiry, 2024)
Final-year university students occupy a fragile transitional space between academic completion and an uncertain future. This article examines future anxiety among final-year students as a multidimensional phenomenon encompassing academic pressure, employability uncertainty, identity formation, family expectations, spiritual struggle, and consequential life decisions under limited control. It employs a constructive conceptual literature review, synthesizing scholarship on university student mental health, career anxiety, career construction and career self-management, religious coping, and contemporary pastoral care. The analysis develops a pastoral accompaniment framework that neither reduces anxiety to a private psychological symptom nor replaces professional mental health or career services. Three constructive findings are proposed: first, future anxiety should be understood as a vocational-existential crisis intensified by final-year transitions; second, pastoral accompaniment contributes through relational presence, meaning-making, spiritual discernment, and referral-aware care; and third, an integrated model should combine stabilization, vocational reframing, and agency-building within accountable communities. The article concludes that pastoral accompaniment is most responsible when it is theologically grounded, psychologically informed, ethically bounded, and collaborative. Its main contribution is a practical-conceptual framework for campus ministries, theological schools, and Christian higher education institutions seeking to accompany final-year students without fabricating empirical claims or spiritualizing distress.